Electrophysiological Evaluation of Common Peroneal Nerve in Chronic Cigarette Smokers. (KYAMC Journal, 2024)
Background: Researchers have identified multiple negative health effects of smoking on the respiratory and cardiovascular systems. It was recently reported that substances in cigarette smoke also have pathological effects on peripheral nerves, which causes neuronal impairment. The common peroneal nerve conduction study is an essential electrodiagnostic test of the lower limb for the detection of peripheral motor nerve dysfunction.Objectives: To assess the potential influence of smoking on the electrophysiological status of common peroneal nerve in young male chronic cigarette smokers.Materials and Methods: This case-control study was conducted in the Department of Physiology, Sir Salimullah Medical College, Dhaka, from July 2017 to June 2018, including thirty male cigarette smokers aged 25 to 40 years. For comparison, another thirty age and BMI-matched healthy male non-smoker subjects were selected in the control group. The electrophysiological parameters (distal latency, amplitude, and motor nerve conduction velocity) of the left common peroneal nerve were evaluated by standard methods in the Department of Neurology, Dhaka Medical College Hospital. For the statistical analysis, an independent t-test was performed.Result: In this study, the mean distal latency of the common peroneal nerve was slightly prolonged, while the mean amplitude was slightly reduced in smokers. However, these changes were not statistically significant. However, the motor nerve conduction velocity was significantly (p ˂ 0.05) slower in cigarette smokers compared to non-smokers.Conclusion: Chronic cigarette smoking causes significant impairment of common peroneal motor nerve conduction, while it does not affect the amplitude in young individuals.KYAMC Journal Volume: 14, No: 03, October 2023: 111-115.